Nickel-zinc ferrite composite material as well as preparation method and application thereof

By mixing nickel-zinc ferrite with sintering additives and preparing through simple process steps, the problems of complex and costly preparation of nickel-zinc ferrite in the prior art are solved, and low-temperature sintering and high-efficiency energy storage conversion are achieved, which is suitable for industrial production.

CN119742170APending Publication Date: 2025-04-01GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510052762.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The sol-gel method used in the prior art for preparing nickel-zinc ferrite has a complex process and is costly, making it difficult to be suitable for industrial production. Especially in the low-temperature co-fired ceramic (LTCC) packaging technology, there is a technical bottleneck in the interface co-sintering between magnetic ferrite and electronic ceramics.

Method used

The nickel-zinc ferrite is mixed with sintering additives (such as BaBiO3, BaBi0.75Co0.25O3, BaBi0.75Cu0.25O3 and BaBi0.75Ni0.25O3) to form a composite powder, and the nickel-zinc ferrite composite material is prepared by wet ball milling, drying, glueing, pressing molding and sintering to achieve low temperature sintering.

Benefits of technology

This method simplifies the process flow, reduces costs, and can achieve LTCC sintering while meeting the performance of each phase, reduces the sintering temperature, and improves the energy storage and conversion efficiency of nickel-zinc ferrite composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742170A_ABST
    Figure CN119742170A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic ferrite materials, and particularly relates to a nickel-zinc ferrite composite material as well as a preparation method and application thereof. According to the invention, the sintering aid easy to soften is added, and after the sintering aid is compounded with the nickel-zinc ferrite and the temperature is raised to the sintering temperature, nickel-zinc ferrite grains are filled with the molten sintering aid to form the composite soft magnetic ferrite, so that the sintering molding temperature of the whole composite material is reduced. Meanwhile, the nickel-zinc ferrite is crisp and low in tenacity, the tenacity of the sintering aid is relatively high, the high compressive strength of the nickel-zinc ferrite is kept by means of the high tenacity of the sintering aid by adding the sintering aid, and processing of ceramic devices is facilitated. The saturation flux density can be stably improved by adding the sintering aid, so that the energy storage and conversion efficiency of the nickel-zinc ferrite composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft ferrite materials, and in particular relates to a nickel-zinc ferrite composite material and a preparation method and application thereof. Background Art

[0002] Nickel-zinc ferrite has excellent soft magnetic properties, such as high magnetic permeability, high frequency, low coercivity and low power loss, making it one of the most critical soft magnetic materials in the electronics industry. Nickel-zinc soft ferrite is widely used in the manufacture of electronic components such as electronic transformers, inductors and coils. In addition, nickel-zinc soft ferrite is also widely used in new energy vehicles, photovoltaic power generation, green lighting and other fields. With the demand for miniaturization and high frequency of electronic products, the performance requirements for nickel-zinc soft ferrite are also increasing. Therefore, people began to study new preparation technologies and high-performance nickel-zinc soft ferrite materials. For example, the various properties of nickel-zinc ferrite can be improved and the sintering temperature can be reduced by compounding conductive polymers with nickel-zinc ferrite, controlling the sintering atmosphere or adding modifying elements such as Mn and Co.

[0003] As electronic information technology develops towards high speed, high frequency, low consumption, broadband and integration, integrated low temperature co-fired ceramic (LTCC: Low Temperature Co-firing Ceramic) packaging and passive integrated devices have become the inevitable choice for solving 5G, 5.5G mobile phones and base station electronic integrated devices. In particular, the interface co-sintering between multi-layer magnetic ferrites and electronic ceramics (inductors and capacitors) in the LTCC raw ceramic tape process has become a technical bottleneck problem that urgently needs to be solved in multi-device integration. Therefore, the development of a new type of nickel-zinc soft ferrite material that can be integrated using LTCC technology so that it can be co-fired with capacitors, etc., is expected to improve the high integration of electronic communication devices.

[0004] In the prior art, sol-gel method and hydrothermal process are commonly used to prepare nickel-zinc ferrite to reduce the sintering temperature and realize LTCC sintering, but due to the complex process and high cost, it is not suitable for industrial production. Summary of the invention

[0005] The purpose of the present invention is to provide a nickel-zinc-ferrite composite material and a preparation method and application thereof. The preparation method provided by the present invention is simple and low-cost, and the obtained nickel-zinc-ferrite composite material can achieve LTCC sintering and reduce the sintering temperature while meeting the performance of each phase.

[0006] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a nickel-zinc ferrite composite material, comprising the following steps:

[0008] Mixing nickel-zinc ferrite and a sintering aid to obtain a composite powder;

[0009] The composite powders are glued, and then dried, pressed and sintered in sequence to obtain the nickel-zinc ferrite composite material;

[0010] The sintering aid includes BaBiO3, BaBi 0.75 Co 0.25 O3, BaBi 0.75 Cu 0.25 O3 and BaBi 0.75 Ni 0.25 One or more of O3.

[0011] Preferably, the chemical composition of the nickel-zinc ferrite is Ni 0.4 Zn 0.6 Fe2O4;

[0012] The mass of the sintering aid is 25-75% of the mass of the nickel-zinc ferrite.

[0013] Preferably, the mixing method is wet ball milling, and the dispersion medium used in the wet ball milling includes one or more of ethanol, deionized water and ethylene glycol; the rotation speed of the wet ball milling is 200-260 r / min, and the time is 8-12 h.

[0014] Preferably, after the mixing, the obtained mixed liquid is dried, and the drying temperature is 50 to 80° C. and the insulation time is 24 to 36 hours.

[0015] Preferably, the reagent used for the bonding includes one or more of polyvinyl alcohol, polystyrene and polypropylene; the mass ratio of the composite powder to the reagent is 100:0.2-1.0.

[0016] Preferably, the drying temperature is 50-80° C., and the insulation time is 24-36 hours.

[0017] Preferably, the pressing temperature is 20-30° C. and the pressure is 4-8 MPa.

[0018] Preferably, the sintering temperature is 850-940° C., and the holding time is 1-3 hours.

[0019] The present invention also provides a nickel-zinc ferrite composite material prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides the use of the nickel-zinc ferrite composite material described in the above technical solution as a soft magnetic material.

[0021] The invention provides a method for preparing a nickel-zinc ferrite composite material, comprising the following steps: mixing nickel-zinc ferrite and a sintering aid to obtain a composite powder; gluing the composite powder, and sequentially drying, pressing and sintering to obtain the nickel-zinc ferrite composite material; the sintering aid comprises BaBiO3, BaBi 0.75 Co 0.25 O3, BaBi 0.75 Cu 0.25 O3 and BaBi 0.75 Ni 0.25 O3 or more. The present invention adds a sintering aid that is easy to soften. After compounding with nickel-zinc ferrite and heating to the sintering temperature, the molten sintering aid fills the nickel-zinc ferrite grains to form a composite soft magnetic ferrite, thereby reducing the sintering molding temperature of the entire composite material. At the same time, the nickel-zinc ferrite itself is relatively brittle and has low toughness, while the sintering aid has relatively high toughness. The addition of the sintering aid, with the help of the high toughness of the sintering aid and the maintenance of the high compressive strength of the nickel-zinc ferrite, is conducive to the processing of ceramic devices. Since nickel-zinc ferrite needs to effectively convert and store energy when working at high frequencies, the present invention can stably increase the saturation magnetic induction intensity by adding a sintering aid, thereby improving the efficiency of energy storage and conversion of the nickel-zinc ferrite composite material. The preparation method provided by the present invention is simple in process and low in cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 hysteresis loops of the nickel-zinc ferrite composite materials prepared in Comparative Example 1 and Examples 1 to 3;

[0023] Figure 2 hysteresis loops of the nickel-zinc ferrite composite materials prepared in Comparative Example 1 and Examples 7 to 9;

[0024] Figure 3 The surface morphology of the nickel-zinc ferrite composite material prepared in Example 2;

[0025] Figure 4 The surface morphology of the nickel-zinc ferrite composite material prepared in Comparative Example 1;

[0026] Figure 5 The surface morphology of the nickel-zinc ferrite composite material prepared in Example 9;

[0027] Figure 6 The initial magnetic permeability curves of the nickel-zinc ferrite composite materials prepared in Comparative Example 1 and Examples 1 to 3 under the test conditions of 1 to 10 MHz and 100 mV;

[0028] Figure 7It is the initial magnetic permeability curve of the nickel-zinc ferrite composite material prepared in Comparative Example 1 and Examples 7 to 9 under the test conditions of 1 to 10 MHz and 100 mV. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing a nickel-zinc ferrite composite material, comprising the following steps:

[0030] Mixing nickel-zinc ferrite and a sintering aid to obtain a composite powder;

[0031] The composite powders are glued, and then dried, pressed and sintered in sequence to obtain the nickel-zinc ferrite composite material;

[0032] The sintering aid includes BaBiO3, BaBi 0.75 Co 0.25 O3, BaBi 0.75 Cu 0.25 O3 and BaBi 0.75 Ni 0.25 One or more of O3.

[0033] The present invention mixes nickel-zinc ferrite and a sintering aid to obtain a composite powder.

[0034] In the present invention, the chemical composition of the nickel-zinc ferrite is preferably Ni 0.4 Zn 0.6 Fe2O4. In the present invention, the particle size of the nickel-zinc ferrite is preferably 1-3 μm, specifically 1 μm, 2 μm, 3 μm. In the present invention, the particle size of the sintering aid is preferably 2-4 μm, specifically 2 μm, 3 μm, 4 μm. In the present invention, the mass of the sintering aid is preferably 25-75% of the mass of the nickel-zinc ferrite, specifically 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%.

[0035] In the present invention, the sintering aid used is easy to soften. After being compounded with nickel-zinc ferrite, the temperature is raised to the sintering temperature, and the molten sintering aid fills the nickel-zinc ferrite grains to form a composite soft magnetic ferrite, thereby reducing the sintering molding temperature of the entire composite material; at the same time, the sintering aid has a relatively high toughness. By adding the sintering aid, with the help of the high toughness of the sintering aid and maintaining the high compressive strength of the nickel-zinc ferrite, it is beneficial to the processing of ceramic devices. Since nickel-zinc ferrite needs to effectively convert and store energy when working at high frequencies, the present invention can stably increase the saturation magnetic induction intensity by adding the sintering aid, thereby improving the efficiency of energy storage and conversion of the nickel-zinc ferrite composite material.

[0036] In the present invention, the mixing method is preferably wet ball milling, and the dispersion medium used in the wet ball milling preferably includes one or more of ethanol, deionized water and ethylene glycol. In the present invention, it is preferred to first mix the sintering aid and nickel-zinc ferrite to obtain a mixed powder; and wet ball mill the mixed powder in the presence of a dispersion medium. In the present invention, the solid-liquid ratio of the mixed powder and the dispersion medium is preferably 1.5 to 2 g / mL, and more preferably 1 to 1.7 g / mL. In the present invention, the rotation speed of the wet ball milling is preferably 200 to 260 r / min, and the time is preferably 8 to 12 h.

[0037] In the present invention, after the mixing, the obtained mixed liquid is preferably dried, and the drying temperature is preferably 50 to 80° C., and the insulation time is preferably 24 to 36 hours.

[0038] In the present invention, the drying step preferably further includes screening. In the present invention, the pore size of the filter used for screening is preferably 50 to 200 meshes, more preferably 100 meshes.

[0039] In the present invention, the sintering aid is preferably obtained by preparation.

[0040] In the present invention, the BaBi 0.75 Cu 0.25 The preparation method of O3 preferably comprises: mixing BaCO3, Bi2O3 and CuO; mixing the obtained mixture with anhydrous ethanol and performing ball milling, and then drying and grinding in sequence to obtain a mixed powder; sintering the mixed powder to obtain BaBi 0.75 Cu 0.25 O3. In the present invention, the mass ratio of BaCO3, Bi2O3 and CuO is preferably 5:6:0.124; the rotation speed of the ball mill is preferably 240r / min, and the time is preferably 8h; the temperature of the drying is preferably 60°C, and the time is preferably 2d. The present invention has no special restrictions on the grinding process, until there is no obvious granularity. In the present invention, the sintering temperature is preferably 725°C, and the holding time is preferably 2h.

[0041] In the present invention, the BaBi 0.75 Ni 0.25 The preparation method of O3 is preferably referred to the BaBi 0.75 Cu 0.25 The preparation method of O3 is just to replace the CuO with NiO, and the mass ratio of BaCO3, Bi2O3 and NiO is preferably 5:6:0.116.

[0042] In the present invention, the preparation method of BaBiO3 is preferably referred to the BaBi 0.75Cu 0.25 The preparation method of O3 is just to not add CuO.

[0043] In the present invention, the BaBi 0.75 Co 0.25 The preparation method of O3 is preferably referred to the BaBi 0.75 Cu 0.25 The preparation method of O3 is to replace the CuO with Co3O4, and the mass ratio of BaCO3, Bi2O3 and Co3O4 is preferably 5:6:0.125.

[0044] After obtaining the composite powder, the present invention glues the composite powder, and sequentially performs drying, compression molding and sintering to obtain the nickel-zinc ferrite composite material.

[0045] In the present invention, the bonding agent preferably includes one or more of polyvinyl alcohol, polystyrene and polypropylene, more preferably polyvinyl alcohol (PVA), and the mass concentration of the polyvinyl alcohol is preferably 5%. In the present invention, the mass ratio of the composite powder to the bonding agent is preferably 100:0.2-1.0, and more preferably 100:0.5. The present invention has no special limitation on the bonding method, and a method well known to those skilled in the art can be used.

[0046] In the present invention, the drying temperature is preferably 50 to 80° C., more preferably 60° C.; the drying time is preferably 24 to 36 hours, more preferably 24 hours.

[0047] In the present invention, the drying preferably further comprises grinding. The present invention has no particular limitation on the grinding process, and the dried product can be ground until there are no obvious particles.

[0048] In the present invention, the temperature of the compression molding is preferably 20 to 30° C., and the pressure is preferably 4 to 8 MPa, and more preferably 6 MPa.

[0049] In the present invention, the sintering temperature is 850-940°C, specifically 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C; the holding time is preferably 1-3h, more preferably 2h. In the present invention, the sintering is preferably carried out in a low-temperature muffle furnace.

[0050] The present invention also provides a nickel-zinc ferrite composite material prepared by the preparation method described in the above technical solution.

[0051] In order to further illustrate the present invention, a nickel-zinc ferrite composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0052] The particle size of the nickel-zinc ferrite used in the subsequent examples is 2 μm, and the particle size of the sintering aid is 3 μm.

[0053] Example 1

[0054] Weigh 5 g of BaCO3 powder and 6 g of Bi2O3 powder and mix them. Place the obtained mixture and 100 mL of anhydrous ethanol in a sealed pot mill and ball-mill at 200 r / min for 8 h. Dry the ball-milled slurry in a constant temperature oven at 60°C for 2 days to obtain a dry material. Put the above dry material into a mortar and grind it thoroughly until there are no obvious particles to obtain a mixed powder. Place the mixed powder in a low-temperature muffle furnace and sinter it at 725°C for 2 h to obtain a sintering aid BaBiO3.

[0055] Weigh 0.15 g of BaBiO3 and 60 g of nickel-zinc ferrite to obtain a mixed powder; place the mixed powder and 170 mL of deionized water in a sealed pot mill, ball mill for 10 h at 220 r / min, dry the ball-milled slurry in a constant temperature oven at 70° C. for 24 h, and then sieve with a 100-mesh screen to obtain a composite powder;

[0056] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly for gluing, dried in a constant temperature oven at 70°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 880°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0057] Example 2

[0058] The sintering aid BaBiO3 was prepared in the manner of Example 1;

[0059] Weigh 0.3 g of BaBiO3 and 60 g of nickel-zinc ferrite to obtain a mixed powder; place the mixed powder and 170 mL of deionized water in a sealed pot mill, ball-mill for 10 h at 240 r / min, dry the ball-milled slurry in a constant temperature oven at 60° C. for 24 h, and then sieve with a 100-mesh screen to obtain a composite powder;

[0060] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly for gluing, dried in a constant temperature oven at 70°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 880°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0061] Example 3

[0062] The sintering aid BaBiO3 was prepared in the manner of Example 1;

[0063] Weigh 0.45 g of BaBiO3 and 60 g of nickel-zinc ferrite to obtain a mixed powder; place the mixed powder and 170 mL of ethylene glycol in a sealed pot mill, ball mill for 8 h at 260 r / min, dry the ball-milled slurry in a constant temperature oven at 80° C. for 36 h, and then sieve with a 100-mesh screen to obtain a composite powder;

[0064] 10 mL of 5% PVA was added dropwise to the above composite powder, stirred evenly for gluing, and then dried in a constant temperature oven at 80°C for 24 hours, and then put into a mortar and fully ground until there were no obvious particles, 0.35 g of the above ground powder was weighed, placed in a mold and pressed at 25°C and 6MPa to obtain a nickel-zinc ferrite composite embryo; the nickel-zinc ferrite composite embryo was placed in a low-temperature muffle furnace and sintered at 880°C for 3 hours to obtain a nickel-zinc ferrite composite material.

[0065] Example 4

[0066] 5 g of BaCO3 powder, 6 g of Bi2O3 powder and 0.125 g of Co3O4 powder were weighed and mixed. The obtained mixture and 100 mL of anhydrous ethanol were placed in a sealed pot mill and ball-milled at 200 r / min for 8 h. The ball-milled slurry was dried in a constant temperature oven at 60 ° C for 2 days to obtain a dry material; the above dry material was put into a mortar and fully ground until there were no obvious particles to obtain a mixed powder; the mixed powder was placed in a low-temperature muffle furnace and sintered at 725 ° C for 2 h to obtain a sintering aid BaBi 0.75 Co 0.25 O3;

[0067] Weigh BaBi 0.75 Co 0.25 O30.15g and nickel-zinc ferrite 60g are mixed to obtain a mixed powder; the mixed powder and 170mL of ethylene glycol are placed in a sealed pot mill, ball-milled at 260r / min for 12h, the ball-milled slurry is dried in a constant temperature oven at 80°C for 24h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0068] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 940°C for 3 hours to obtain a nickel-zinc ferrite composite material.

[0069] Example 5

[0070] The sintering aid BaBi was prepared in the same manner as in Example 4. 0.75 Co 0.25 O3;

[0071] Weigh BaBi 0.75 Co 0.25 O30.3g and 60g of nickel-zinc ferrite were mixed to obtain a mixed powder; the mixed powder and 170mL of ethylene glycol were placed in a sealed pot mill, ball-milled at 260r / min for 12h, the ball-milled slurry was dried in a constant temperature oven at 80°C for 36h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0072] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 940°C for 3 hours to obtain a nickel-zinc ferrite composite material.

[0073] Example 6

[0074] The sintering aid BaBi was prepared in the same manner as in Example 4. 0.75 Co 0.25 O3;

[0075] Weigh BaBi 0.75 Co 0.25 O30.45g and nickel-zinc ferrite 60g, to obtain a mixed powder; the mixed powder and 170mL ethylene glycol were placed in a sealed pot mill, ball-milled at 260r / min for 8h, the ball-milled slurry was dried in a constant temperature oven at 60°C for 36h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0076] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 30 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 940°C for 3 hours to obtain a nickel-zinc ferrite composite material.

[0077] Example 7

[0078] Weigh 5 g of BaCO3 powder, 6 g of Bi2O3 powder and 0.124 g of CuO powder and mix them. Place the obtained mixture and 100 mL of anhydrous ethanol in a sealed pot mill and ball mill at 240 r / min for 8 h. Dry the ball-milled slurry in a constant temperature oven at 60 ° C for 2 days to obtain a dry material. Put the above dry material into a mortar and grind it thoroughly until there are no obvious particles to obtain a mixed powder. Place the mixed powder in a low-temperature muffle furnace and sinter it at 725 ° C for 2 h to obtain a sintering aid BaBi 0.75 Cu 0.25 O3;

[0079] Weigh BaBi 0.75 Cu 0.25 O30.15g and nickel-zinc ferrite 60g are mixed to obtain a mixed powder; the mixed powder and 170mL of anhydrous ethanol are placed in a sealed pot mill, ball-milled at 200r / min for 10h, the ball-milled slurry is dried in a constant temperature oven at 60°C for 24h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0080] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 30 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 900°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0081] Example 8

[0082] The sintering aid BaBi was prepared in the same manner as in Example 7. 0.75 Cu 0.25 O3;

[0083] Weigh BaBi 0.75 Cu 0.25O30.3g and 60g of nickel-zinc ferrite were mixed to obtain a mixed powder; the mixed powder and 170mL of anhydrous ethanol were placed in a sealed pot mill, and ball-milled at 200r / min for 10h, the ball-milled slurry was dried in a constant temperature oven at 60°C for 24h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0084] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 30 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 900°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0085] Example 9

[0086] The sintering aid BaBi was prepared in the same manner as in Example 7. 0.75 Cu 0.25 O3;

[0087] Weigh BaBi 0.75 Cu 0.25 O30.45g and nickel-zinc ferrite 60g are mixed to obtain a mixed powder; the mixed powder and 170mL of anhydrous ethanol are placed in a sealed pot mill, ball-milled at 200r / min for 10h, the ball-milled slurry is dried in a constant temperature oven at 60°C for 24h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0088] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 30 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 900°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0089] Example 10

[0090] Weigh 5 g of BaCO3 powder, 6 g of Bi2O3 powder and 0.116 g of NiO powder and mix them. Place the obtained mixture and 100 mL of anhydrous ethanol in a sealed pot mill and ball mill at 240 r / min for 8 h. Dry the ball-milled slurry in a constant temperature oven at 60 ° C for 2 days to obtain a dry material. Put the above dry material into a mortar and grind it thoroughly until there are no obvious particles to obtain a mixed powder. Place the mixed powder in a low-temperature muffle furnace and sinter it at 725 ° C for 2 h to obtain a sintering aid BaBi 0.75 Ni0.25 O3;

[0091] Weigh BaBi 0.75 Ni 0.25 O30.15g and nickel-zinc ferrite 60g are mixed to obtain a mixed powder; the mixed powder and 170mL of anhydrous ethanol are placed in a sealed pot mill, ball-milled at 260r / min for 12h, the ball-milled slurry is dried in a constant temperature oven at 60°C for 24h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0092] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 80°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 920°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0093] Embodiment 11

[0094] The sintering aid BaBi was prepared in the same manner as in Example 10. 0.75 Ni 0.25 O3;

[0095] Weigh BaBi 0.75 Ni 0.25 O30.3g and 60g of nickel-zinc ferrite were mixed to obtain a mixed powder; the mixed powder and 170mL of anhydrous ethanol were placed in a sealed pot mill, ball-milled at 260r / min for 12h, the ball-milled slurry was dried in a constant temperature oven at 60°C for 24h, and then sieved with a 100-mesh screen to obtain a composite powder;

[0096] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 80°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 920°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0097] Example 12

[0098] The sintering aid BaBi was prepared in the same manner as in Example 10. 0.75 Ni 0.25 O3;

[0099] Weigh BaBi 0.75 Ni 0.25O30.45g and nickel-zinc ferrite 60g to obtain a mixed powder; the mixed powder and 170mL of anhydrous ethanol were placed in a sealed pot mill, ball-milled at 260r / min for 12h, the ball-milled slurry was dried in a constant temperature oven at 60°C for 2d, and then sieved with a 100-mesh screen to obtain a composite powder;

[0100] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 80°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 920°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0101] Comparative Example 1

[0102] Weigh 60 g of nickel-zinc ferrite to obtain a basic powder; place the basic powder and 170 mL of deionized water in a sealed pot mill, ball-mill for 10 h at 220 r / min, dry the ball-milled slurry in a constant temperature oven at 70° C. for 24 h, and then sieve with a 100-mesh screen to obtain a composite powder;

[0103] 10 mL of 5% PVA was added dropwise to the composite powder, stirred evenly, and then dried in a constant temperature oven at 70°C for 36 hours, and then put into a mortar and ground thoroughly until there were no obvious particles. 0.35 g of the ground powder was weighed, placed in a mold and pressed at 25°C and 6 MPa to obtain a nickel-zinc ferrite composite green body; the nickel-zinc ferrite composite green body was placed in a low-temperature muffle furnace and sintered at 880°C for 2 hours to obtain a nickel-zinc ferrite composite material.

[0104] Test Case

[0105] Test Example 1

[0106] Figure 1 is the hysteresis loop of the nickel-zinc ferrite composite material prepared in Comparative Example 1 and Examples 1 to 3, wherein x=0 represents Comparative Example 1, x=0.25 represents Example 1, x=0.5 represents Example 2, and x=0.75 represents Example 3. Figure 1 The results show that the nickel-zinc ferrite composite materials prepared in Examples 1 to 3 have higher saturation magnetic induction intensity and lower coercive force under low temperature sintering conditions.

[0107] Figure 2 is the hysteresis loop of the nickel-zinc ferrite composite material prepared in Comparative Example 1 and Examples 7 to 9, wherein x=0 represents Comparative Example 1, x=0.25 represents Example 7, x=0.5 represents Example 8, and x=0.75 represents Example 9. Figure 2 The results show that the nickel-zinc ferrite composite materials prepared in Examples 7 to 9 have higher saturation magnetic induction intensity and lower coercive force under low temperature sintering conditions.

[0108] Test Example 2

[0109] Figure 3 The surface morphology of the nickel-zinc ferrite composite material prepared in Example 2 is shown in FIG. Figure 4 The surface morphology of the nickel-zinc ferrite composite material prepared in Comparative Example 1 is as follows: Figures 3-4 It can be seen that compared with the nickel-zinc ferrite composite material prepared in Comparative Example 1, the nickel-zinc ferrite composite material prepared in Example 2 has more uniform and dense grains, indicating that the nickel-zinc ferrite composite material prepared under the conditions of Example 2 can obtain a better surface morphology.

[0110] Figure 5 The surface morphology of the nickel-zinc ferrite composite material prepared in Example 9 is as follows: Figure 5 and Figure 4 It can be seen that compared with the nickel-zinc ferrite composite material prepared in Comparative Example 1, the nickel-zinc ferrite composite material prepared in Example 9 has more uniform and dense grains, indicating that the nickel-zinc ferrite composite material prepared under the conditions of Example 9 can obtain a better surface morphology.

[0111] Test Example 3

[0112] The initial magnetic permeability of the nickel-zinc ferrite composite materials prepared in Examples 1 to 12 was tested, and the test conditions included: a measuring voltage of 100 mV, a winding number of 1 turn, a measuring temperature of room temperature, a measuring method of sweep frequency testing, and test frequencies of 1 MHz, 2 MHz, 4 MHz and 10 MHz, respectively; the inductance measurement method was used to measure, after a wire was wound around the magnetic core of the toroidal magnetic core, it was placed in a confined space, and the inductance at both ends of the wire was measured by an impedance analyzer, and the initial magnetic permeability was derived according to the test inductance;

[0113] The saturation magnetic induction intensity and coercive force of the nickel-zinc ferrite composite materials prepared in Examples 1 to 12 were tested. The test process was as follows: before the test, the sample was weighed and the equipment was calibrated. The hysteresis loop test was performed under a VSM vibrating magnetometer. The obtained results were divided by the sample mass to obtain the magnetic induction intensity and coercive force. The test conditions were room temperature and an applied magnetic field of ±5000Oe.

[0114] The initial magnetic permeability, saturation magnetic induction intensity and coercive force of the nickel-zinc ferrite composite materials prepared according to Examples 1 to 12 can prove their magnetic properties. The results are shown in Tables 1 and 2.

[0115] Table 1 Initial magnetic permeability test results of nickel-zinc ferrite composite materials

[0116]

[0117] Table 2 Saturation magnetic induction intensity and coercive force test results of nickel-zinc ferrite composite materials

[0118]

[0119]

[0120] It can be seen from Table 1 and Table 2 that the nickel-zinc ferrite composite material provided by the present invention has a reasonable initial magnetic permeability and good magnetic properties.

[0121] Figure 6 is the initial magnetic permeability of the nickel-zinc ferrite composite materials prepared in Comparative Example 1 and Examples 1 to 3 under the test conditions of 1 to 10 MHz and 100 mV, wherein x=0 represents Comparative Example 1, x=0.25 represents Example 1, x=0.5 represents Example 2, and x=0.75 represents Example 3. Figure 6 The results show that the nickel-zinc ferrite composite material provided by the present invention has a stable and high initial magnetic permeability under low temperature sintering conditions.

[0122] Figure 7 is the initial magnetic permeability of the nickel-zinc ferrite composite materials prepared in Comparative Example 1 and Examples 7 to 9 under the test conditions of 1 to 10 MHz and 100 mV, wherein x=0 represents Comparative Example 1, x=0.25 represents Example 7, x=0.5 represents Example 8, and x=0.75 represents Example 9. Figure 7 The results show that the nickel-zinc ferrite composite material provided by the present invention has a stable and high initial magnetic permeability under low temperature sintering conditions.

[0123] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a nickel-zinc ferrite composite material, characterized in that: The following steps are involved: Mixing nickel-zinc ferrite and a sintering aid to obtain a composite powder; The composite powders are glued, and then dried, pressed and sintered in sequence to obtain the nickel-zinc ferrite composite material; The sintering aid includes BaBiO3, BaBi 0.75 Co 0.25 O3, BaBi 0.75 Cu 0.25 O3 and BaBi 0.75 Ni 0.25 One or more of O3.

2. The preparation method according to claim 1, characterized in that: The chemical composition of the nickel-zinc ferrite is Ni 0.4 Zn 0.6 Fe2O4; The mass of the sintering aid is 25-75% of the mass of the nickel-zinc ferrite.

3. The preparation method according to claim 1, characterized in that: The mixing method is wet ball milling, and the dispersion medium used in the wet ball milling includes one or more of ethanol, deionized water and ethylene glycol; the rotation speed of the wet ball milling is 200-260 r / min, and the time is 8-12 hours.

4. The preparation method according to claim 3, characterized in that: After the mixing, the obtained mixed liquid is dried, the drying temperature is 50-80° C., and the insulation time is 24-36 hours.

5. The preparation method according to claim 1, characterized in that: The reagents used for bonding include one or more of polyvinyl alcohol, polystyrene and polypropylene; the mass ratio of the composite powder to the reagent is 100:0.2-1.

0.

6. The preparation method according to claim 1 or 5, characterized in that: The drying temperature is 50-80° C., and the insulation time is 24-36 hours.

7. The preparation method according to claim 6, characterized in that: The temperature of the compression molding is 20-30° C., and the pressure is 4-8 MPa.

8. The preparation method according to claim 1 or 7, characterized in that: The sintering temperature is 850-940° C., and the heat preservation time is 1-3 hours.

9. The nickel-zinc ferrite composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nickel-zinc ferrite composite material according to claim 9 as a soft magnetic material.